Grip Ability Test in Rheumatoid Arthritis Patients: Relationship With Disease Activity and Hand-Specific Self-Report Questionnaires - Çiğdem BİRCAN and Nihan ERDİNÇ GÜNDÜZ and Ayşegül TEKGÜL and Pınar ÇETİN and Fatoş ÖNEN and Ramazan KIZIL and Selmin GÜLBAHAR (Archives of Rheumatology, 2014)
Objectives: The aim of this study was to investigate the relationship between the Grip Ability Test (GAT) and disease activity, and hand-specific self-report questionnaires in patients with rheumatoid arthritis (RA). Patients and methods: The study included 65 RA patients (55 females, 10 males; mean age 55±11 years; range 24 to 74 years) who were diagnosed according to the American College of Rheumatology/European League Against Rheumatism 2010 criteria. Duration of disease and duration of morning stiffness were recorded. The number of tender and swollen joints and hand deformities were identified. A 100-mm visual analog scale (VAS) was used to assess the intensity of pain at rest and pain during activities of daily living, and stiffness. The grip strength was measured in both hands by a Jamar dynamometer. Flexion deficit in fingers II-V was recorded as the distance from the distal palmar crease to the tip of the fingers. The disease activity was measured with the Disease Activity Score 28. Health Assessment Questionnaire, hand and finger function subscale of Arthritis Impact Measurement Scale 2, and Duruoz Hand Index were completed by all patients. Results: The mean duration of disease was 10.2±8.2 years (range 1 to 42 years). Significant positive correlations were found between GAT score and duration of morning stiffness, VAS-pain during activities of daily living, VAS-stiffness, finger flexion deficit of dominant hand, Disease Activity Score 28, Health Assessment Questionnaire, Arthritis Impact Measurement Scale 2 hand/finger function subscale, and Duruoz Hand Index (r=0.261 to 0.639, p<0.05). There were significant negative correlations between the GAT score and dominant (r= -0.505, p<0.001) and non-dominant hand (r= -0.399, p=0.001) grip strength. No significant correlation was found between the GAT and duration of disease, and VAS-pain at rest. Conclusion: Weak to moderate correlations were found between the GAT and disease activity, and hand-specific self-report questionnaires in patients with RA. An evaluation of patients using a performance-based test such as GAT as well as clinical and laboratory assessments may provide important additional information about the patients’ hand disability.